2014
DOI: 10.1007/s10517-014-2409-0
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Histone Deacetylase Inhibitor During Neonatal Period Changes Emotionality of Adult Male 129Sv Mice

Abstract: Environmental factors acting during the neonatal period affected the formation of phenotype of adult animals via epigenetic modifications of the genome, e.g. histone acetylation. We studied the effects of blockage of histone deacetylases with sodium valproate on week 1 of life on the behavioral pattern of adult male 129Sv mice. The results of behavioral tests attest to long-term changes in emotional, but not cognitive pattern of adult animals after sodium valproate administration, which manifested in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…an animal model of ASD [36,37,40,44,57]. However, VPA exposure during early postnatal life can also induce ASD -like behavioral phenotypes in mice [35,56] and ferrets [45]. These studies indicate that VPA exposure can induce an animal model of ASD over a wide range of exposure durations, from the second trimester to infancy.…”
Section: Plos Onementioning
confidence: 81%
See 1 more Smart Citation
“…an animal model of ASD [36,37,40,44,57]. However, VPA exposure during early postnatal life can also induce ASD -like behavioral phenotypes in mice [35,56] and ferrets [45]. These studies indicate that VPA exposure can induce an animal model of ASD over a wide range of exposure durations, from the second trimester to infancy.…”
Section: Plos Onementioning
confidence: 81%
“…Developmental VPA exposure can induce ASD-like behavioral phenotypes, including reduced social interaction in mice [35,56], rats [36][37][38], common marmosets [57], and ferrets [45]. VPA-induced behavioral deficits might be associated with cortical dysgenesis characterized by increasing neuron numbers and cortical thickening in humans [39], mice [41,43], and rats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal and neonatal exposure to VPA induces ASD-like behavioral abnormalities in various mammalian species ( Miyazaki et al, 2005 ; Yochum et al, 2008 ; Mychasiuk et al, 2012 ; Favre et al, 2013 ; Burenkova et al, 2014 ; Yasue et al, 2018 ), including ferrets ( Krahe et al, 2016 ). These behavioral abnormalities are believed to be associated with cerebral cortical abnormalities that have been reported as the effect of developmental VPA exposure in ferrets ( Sawada et al, 2021 ) and other mammalian species ( Wood et al, 2014 ; Fujimura et al, 2016 ; Lauber et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Valproic acid (VPA), a well-known antiepileptic/anticonvulsant drug, also acts as an inhibitor of histone deacetylases 1 and 2 ( Göttlicher et al, 2001 ; Phiel et al, 2001 ). Many studies have reported autism spectrum disorder (ASD)-like behavioral abnormalities induced by VPA exposure during prenatal and neonatal periods in various mammalian species such as mice ( Yochum et al, 2008 ; Burenkova et al, 2014 ), rats ( Miyazaki et al, 2005 ; Mychasiuk et al, 2012 ; Favre et al, 2013 ), common marmosets ( Yasue et al, 2018 ), and ferrets ( Krahe et al, 2016 ). These behavioral abnormalities are believed to be associated with cerebral cortical abnormalities caused by developmental VPA exposure ( Sabers et al, 2014 ; Wood et al, 2014 ; Fujimura et al, 2016 ; Lauber et al, 2016 ; Sawada et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fetal alcohol spectrum disorder (FASD) and fetal valproate syndrome are neurodevelopmental disorders (Lindhout and Schmidt, 1986;May et al, 2014;Ornoy, 2009;Rihtman et al, 2013;Riley et al, 2011) characterized by behavioral and physiological abnormalities that include sensory processing deficits, which in turn are associated with deficits in social interaction and autistic behavior (Carr et al, 2010;Nanson, 1992;Rihtman et al, 2013;Stevens et al, 2013;Williams et al, 2001). While there is extensive evidence that developmental exposure to alcohol or valproic acid (VPA) can remarkably affect social interactions in rodents (Meyer and Riley, 1986;Kelly et al, 2000;Varlinskaya and Mooney, 2014;Burenkova et al, 2014;Yochum et al, 2008;Charles Lawrence et al, 2008), much less is known about the effects of these teratogenic drugs in the social behavior of gyrencephalic species. A more complex cortex leads to more sophisticated behavior, which might be even more susceptible to the effects of teratogens.…”
Section: Introductionmentioning
confidence: 99%